The structure of tort law - Jansen, Nils; Steel, Sandy (Oxford : Oxford University Press, 2021)
This English translation makes available to anglophone readers a modern classic of German tort theory. It argues that modern German tort law is faced with doctrinal tensions based on problematic theoretical assumptions which stem from historical conceptions of tortious liability, inappropriate to modern times. From a theoretical perspective, it argues against the prevalent doctrinal view in Germany that conceives of tortious liability as split between two tracks - a fault-basedtrack and a strict liability track - each with different normative foundations.
This edition also issued in print: 2021.
Translated from the German.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on December 14, 2021).
Keywords: Torts -- Germany